Thermal and Mechanical Investigation of Friction Stir Welding with Disparate Materials AA6061 and AA7075 - K, Sabari; A, Muniappan (Recent Patents on Mechanical Engineering, 2024)
Background: The primary objective of this study is to assess the impact of welding conditions on the mechanical properties of friction stir-welded butt joints created from two distinct aluminium alloys, namely, AA6061 and AA7075. Friction stir welding (FSW), known for its innovation and low-energy solid-state bonding technique, was employed in this research. Methods: FSW experiments were carried out on both AA6061 and AA7075 alloys using a computer numerical control (CNC) machine. The selection and design of the tool geometry were meticulous, with an emphasis on new pin profiles that are nearly flat at the weld contact point. Precisely, four distinct tool geometries were machined from HC-HCr (High carbon, high chromium steel): Circular, Square, Tapered third, and Triangular. Critical process variables that significantly influence weld quality include rotation speed (800 rpm-1400 rpm) and traverse speed (12 to 25 mm/min). These variables were carefully optimized to achieve flawless welds. During the friction stir welding process, the nugget zone undergoes significant deformation, leading to the formation of a new microstructure that substantially impacts the mechanical properties of the joint. Results: This study comprehensively investigates the thermal and mechanical properties of friction stir welding using aluminium alloys AA6061 and AA7075, considering various tool shapes. Among the four tool shapes employed, two were found to yield higher hardness values (referred to as BH). Notably, the square-shaped tool produced the highest temperature, reaching up to 690ºC, as determined by thermocouple readings. Based on the findings, the optimal FSW parameters for enhancing hardness involve an axial feed and spindle speed of 800 rpm combined with a feed rate of 15 mm/min. These parameters were identified as crucial for achieving the desired mechanical properties in the friction stir-welded joints. Conclusion: This study presents new developments in FSW technology, which may have patent implications.
Keywords: AA7075